2012
DOI: 10.1111/j.1365-2966.2012.21676.x
|View full text |Cite
|
Sign up to set email alerts
|

Understanding hydrogen recombination line observations with ALMA and EVLA

Abstract: Hydrogen recombination lines are one of the major diagnostics of H ii region physical properties and kinematics. In the near future, the Expanded Very Large Array (EVLA) and the Atacama Large Millimeter Array (ALMA) will allow observers to study recombination lines in the radio and submillimetre regimes in unprecedented detail. In this paper, we study the properties of recombination lines, in particular at ALMA wavelengths. We find that such lines will lie in almost every wideband ALMA set‐up and that the line… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 47 publications
1
38
0
1
Order By: Relevance
“…A possible drawback of (sub)mm RLs is that the free-free continuum may be contaminated by dust emission. Another problem is that they are out of LTE more easily than cm lines, so their interpretation may require careful modeling (e.g., Jiménez-Serra et al 2011;Peters et al 2012). As shown below, our simple LTE interpretation seems to be reasonable, but it is possible that a significant fraction of the 1.3-mm continuum comes from dust in the line of sight.…”
Section: Appendix A: Linewidth Of Recombination Linesmentioning
confidence: 88%
See 1 more Smart Citation
“…A possible drawback of (sub)mm RLs is that the free-free continuum may be contaminated by dust emission. Another problem is that they are out of LTE more easily than cm lines, so their interpretation may require careful modeling (e.g., Jiménez-Serra et al 2011;Peters et al 2012). As shown below, our simple LTE interpretation seems to be reasonable, but it is possible that a significant fraction of the 1.3-mm continuum comes from dust in the line of sight.…”
Section: Appendix A: Linewidth Of Recombination Linesmentioning
confidence: 88%
“…Millimeter (mm) RLs are in principle better suited to giving the central velocity of the system because they are more optically thin, much less pressure broadened, and intrinsically brighter than centimeter (cm) lines (e.g., Gordon & Sorochenko 2002;Peters et al 2012). However, longer wavelength lines are a valuable complement because they are sensitive to the gas density.…”
Section: Introductionmentioning
confidence: 99%
“…Two are the most chemically rich in our study (G339.11, and G336.98, which, from its radio SED is expected to be one of our youngest Hii regions), while the other (G302.02) shows no molecular emission across the Hii region (neither in the H29α nor CS passbands), suggesting that the complex molecules have been destroyed by the ionising radiation. Peters et al (2012) implemented the modelling of RRL line profiles detectable at JVLA and ALMA wavelengths into RADMC-3D using non-LTE methods to understand line shapes. The test cases they used to demonstrate the code focussed on infalling and outflowing RRL emission, and under which conditions these signatures would be detectable.…”
Section: Rrl Velocity Gradientsmentioning
confidence: 99%
“…As previously noted, they allowed for spherical outflow and found that line shapes can be asymmetric. Peters, Longmore, & Dullemond (2012) ii. The wind is optically thick to free-free opacity.…”
Section: Radio Recombination Line Modelingmentioning
confidence: 99%